2022
DOI: 10.1126/scitranslmed.abj2658
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical evaluation of the LRRK2 inhibitor DNL201 for Parkinson’s disease

Abstract: Mutations in leucine-rich repeat kinase 2 ( LRRK2 ) are the most common genetic risk factors for Parkinson’s disease (PD). Increased LRRK2 kinase activity is thought to impair lysosomal function and may contribute to the pathogenesis of PD. Thus, inhibition of LRRK2 is a potential disease-modifying therapeutic strategy for PD. DNL201 is an investigational, first-in-class, CNS-penetrant, selective, ATP-competitive, small-molecule LRRK2 kinase inhibitor. In preclinical models, DNL201 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 46 publications
6
97
0
Order By: Relevance
“…5 Efforts to develop LRRK2 inhibitors have largely focused on small molecule ATP competitive-binding kinase inhibitors such as MLi-2 and DNL201. 6,7 While these small molecule inhibitors are successful at downregulating LRRK2 kinase activity, there was some evidence of toxicities observed that may be limited to particular animal models. 6,8 Protein−protein interactions (PPIs) are a major driving force for the activation of many cellular pathways and associated disease pathologies, making them an attractive target for drug discovery.…”
mentioning
confidence: 99%
“…5 Efforts to develop LRRK2 inhibitors have largely focused on small molecule ATP competitive-binding kinase inhibitors such as MLi-2 and DNL201. 6,7 While these small molecule inhibitors are successful at downregulating LRRK2 kinase activity, there was some evidence of toxicities observed that may be limited to particular animal models. 6,8 Protein−protein interactions (PPIs) are a major driving force for the activation of many cellular pathways and associated disease pathologies, making them an attractive target for drug discovery.…”
mentioning
confidence: 99%
“…The discovery that LRRK2 deleterious variants lead to increased kinase activity 9,18 laid the foundations for LRRK2 kinase inhibitors as a potential treatment for LRRK2 ‐PD (Table 3). The main LRRK2 inhibitors currently developed are DNL151 and DNL201, which already passed phase I and Ib clinical trials with most of the participants developing no or mild adverse effects at clinically relevant doses (https://www.denalitherapeutics.com, 2021) 124 . An indirect mechanism proposed to control LRRK2 activity is the inhibition of its GTPase activity, which demonstrated positive outcomes both in vitro and in vivo , with reduced LRRK2 autophosphorylation and neuroinflammation, as well as suppression of neurodegeneration.…”
Section: Therapymentioning
confidence: 99%
“…In mice, histopathological abnormalities have been reported in kidneys after LRRK2 inhibition 130 and, in primates, LRRK2 inhibition produced reversible lamellar bodies in the lungs, but they did not lead to any clinical manifestation 131 . In the DNL151/201 phase 1/1b clinical trials no significant alteration in the pulmonary or renal function emerged (https://www.denalitherapeutics.com, 2021) 124 . In addition, loss of function LRRK2 variants reduce LRRK2 protein levels but are not associated with any phenotypic or pathological alteration 132 .…”
Section: Therapymentioning
confidence: 99%
See 2 more Smart Citations